2016
DOI: 10.17576/mjas-2016-2002-09
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone as a New Fluorescent Sensor for Nitrate Ion

Abstract: In this study, non-conjugated polyvinylpyrrolidone(PVP) was investigated for the first time as the potential polymeric material to sense nitrate ions by fluorescence spectroscopy. The PVP was diluted into various concentrations (3-10%) and they were used to sense the nitrate ions in different concentrations (0.1-100 mM). The PVP showed two excitation peaks at 285 and 330 nm due to the presence of C=O and N-C groups, respectively. One strong emission at 400 or 408 nm was observed with the excitation at 285 or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…53 PVP displayed a blue color which associated with the π*→π band transition in PVP molecules, 54 while the presence of C=O and N-C groups in PVP was thought to be responsible for the UV color. 55 The green color may be caused by the vacancy and/or interstitial states in the structure via self-activated centers. 56 The colors released by different samples have also been described using color coordinates derived from the CIE 1931 chromaticity diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…53 PVP displayed a blue color which associated with the π*→π band transition in PVP molecules, 54 while the presence of C=O and N-C groups in PVP was thought to be responsible for the UV color. 55 The green color may be caused by the vacancy and/or interstitial states in the structure via self-activated centers. 56 The colors released by different samples have also been described using color coordinates derived from the CIE 1931 chromaticity diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The enormous reduction in fluorescence intensity of Trp in the presence of PVP 40 (Figure ) could be due to the fact that the absorption wavelength of PVP 40 ranges from 230 to 400 nm. The PVP 40 exhibits two excitation peaks due to the presence of CO and NC groups at 285 and 330 nm, respectively . Therefore, energy transfer may be taking place from the excited Trp to PVP 40, causing a significant decrease in the emission intensity of Trp.…”
Section: Resultsmentioning
confidence: 99%
“…The PVP 40 exhibits two excitation peaks due to the presence of C=O and N≡C groups at 285 and 330 nm, respectively. 50 Therefore, energy transfer may be taking place from the excited Trp to PVP 40, causing a significant decrease in the emission intensity of Trp. Other mechanisms such as sphere-of-action quenching (vide infra) 34 and self-aggregation of Trp molecules in the presence of PVP 40 could also cause such a drastic reduction in fluorescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Polyvinyl pyrrolidone (PVP) has several advantages in terms of flexibility, environmental stability, non-toxic and biodegradable. Tang et al [24] have reported their work on nitrate detection using PVP based on a fluorescent sensor. From their research, its shows that the PVP polymer can detect nitrate ions.…”
Section: Introductionmentioning
confidence: 99%